THE DEVELOPMENT OF COUNTRYSIDE WALKING TOURISM IN THE TIME OF THE POST-COVID CRISIS - Milojković, Danka; Nikolić, Milena; Milojković, Katarina (Economics of Agriculture, 2023)
With low investment, countryside walking tourism contributes to the rapid recovery of rural tourism in the post-covid time. The research purpose is to examine factors that impact the interest of tourists in the state-supported countryside walking tourism. The sample consisted of 467 respondents from the general public. The SPSS software was used for processing data. The results indicated that safety, content, and price are the most influential factors. For females, slightly more important factors were related to the possibility of consuming authentic food and beverages, buying traditional handmade products, the inclusion of the local population, and the well-being of urban residents. A village, with authentic local houses and cuisine, and local tour guides, are the epicenter of countryside walking tourism. Embedding countryside walking tourism in sustainable rural tourism development policies is recommended. The research contributes to the integration between sustainable rural development and sustainable tourism development.